Investigating the Bone Toxicity of Florfenicol in Rats: A Histopathological, Metabolomic, and Osteo-Endocrine Biomarker Evaluation - Fadhil, Samer Riyadh; Alsayyid, Qasim Zghair (American Journal of Biology and Natural Sciences, 2025)
Florfenicol is a synthetic broad-spectrum antimicrobial efficacy is well documented, limited attention has been given to its potential systemic toxicity, especially on skeletal tissues. Considering its structural similarity to chloramphenicol and its known mitochondrial inhibitory effects, this study aimed to evaluate the possible bone toxicity of florfenicol in a controlled rat model using histopathological, biochemical, and metabolomic approaches. Thirty-two adults male Wistar rats were randomly divided into four groups: control, low-dose florfenicol (10 mg/kg), high-dose florfenicol (30 mg/kg), and a recovery group (30 mg/kg with 14-day washout). Treatments were administered orally once daily for 28 days. Femoral and tibial bone samples were collected for histopathological examination using hematoxylin and eosin, and TRAP staining. Serum was analyzed for bone turnover markers including osteocalcin, CTX, and bone-specific alkaline antibiotic widely used in veterinary practice, particularly for respiratory and enteric infections in livestock and aquaculture. While its phosphatase. Metabolomic profiling was performed using LC-MS to detect changes in hydroxyproline, citrate, lactate, and inflammatory cytokines. Results showed significant cortical thinning, trabecular disruption, and increased osteoclast activity in high-dose groups. Serum analysis revealed elevated CTX and reduced osteocalcin levels, indicating enhanced bone resorption and impaired formation. Metabolomic analysis supported mitochondrial dysfunction, showing altered TCA cycle intermediates and elevated oxidative stress markers. Partial recovery was observed following drug withdrawal. In conclusion, prolonged florfenicol exposure induced bone tissue alterations in rats, possibly via mitochondrial disruption and oxidative stress. These findings suggest a need for caution in florfenicol use, especially during developmental stages in veterinary patients.